E-Banking Need and Benefits in Indian Economy and Current Financial Innovations in E-banking in India - Archana Salim (PT FORMOSA CENDEKIA GLOBAL, 2022)
A strong banking sector can be termed as lifeline of an economy. It is one of the fastest growing sectors in India. Because the future of banking will be driven by major technological changes and will transform drastically. The future of Banking is 'Digital’. The covid -19 pandemic has re-designed our lives in terms of how we work, how we shop, even how we bank and this has led to major change in customer behaviour. This paper focused on the importance of e-Banking ,although e-Banking system provide us with easy access to banking services, they have introduced new business challenges .This paper enlightens the knowledge light on new innovations in banking sector.